Development and good government. Application to the Venezuelan case - González Silbaran, Carlos; Miranda Delgado, Rafael Gustavo (Teoría y Praxis, 2022)
Development and good Government are two objectives of high social and their presence or absence conditions the quality of life of citizens. In Venezuela there have been problems in development and good Government in recent years. Therefore, the research seeks to answer two questions: How important is good Government for development? And what have been the characteristics of the Government of Venezuela in recent years? The article states that good Government is determinant for the development process, and that Venezuela during the years of study can be characterized as ungovernable.